An inhibitory action of chitosan nanoparticles against pathogenic bacteria and fungi and their potential applications as biocompatible antioxidants. (January 2018) - MubarakAli, D.; LewisOscar, F.; Gopinath, V.; Alharbi, Naify S.; Alharbi, Sulaiman Ali; Thajuddin, N.
Abstract: Chitosan is the second most abundant polymer obtained from the byproduct of seafood. Chitosan and its derivatives and chitosan loaded drugs are the recent area of interest against microbial pathogenesis. The cationic chitosan nanoparticles (ChNPs) interact with the anionic surfaces of the microbial cell membrane, which promotes antimicrobial activity. Although, ChNPs are potential against pathogenic microbes, selection of adaptable, suitable and cost effective synthesis method is much important. In the present study, ChNPs were synthesized adopting ionic gelation using sodium tripolyphosphate as a cross linking agent and characterized by FTIR, DLS, SEM and TEM analysis. ChNPs were investigated for antimicrobial activity against bacterial ( Escherichia coli and Staphylococcus aureus ) and fungal ( Candida albicans ) pathogens. ChNPs showed bactericidal activity at the lower minimum inhibitory concentration of about 40–80 μg mL −1 . Interestingly, ChNPs exhibits biocompatible antioxidant property by inhibiting DPPH free radicals at 76% and also proven to be a potential candidate against the microbial pathogenesis with an inevitable applications in biomedicine. Graphical abstract: Image 1 Highlights: Optimized protocol for the synthesis of chitosan nanoparticles. ChNPs exhibits antimicrobial effect against pathogenic bacteria and fungi. ChNPs exhibits superior antioxidant property than natural antioxidants. ChNPs exhibits superior biocompatible property.